Effect of nebivolol vs. hydrochlorothiazide on the walking capacity in hypertensive patients with intermittent claudication - Diehm, Curt; Pittrow, David; Lawall, Holger (Journal of hypertension, 2011)
Aims - Whereas product labels of beta blockers list peripheral arterial disease (PAD) as a contraindication, current PAD guidelines state otherwise. We aimed to evaluate the clinical efficacy and safety of the ß1 selective blocker nebivolol in hypertensive patients with PAD. - Methods and results - This multicentre, prospective, double-blind, active controlled, parallel-group study compared once-daily treatment with nebivolol (Neb) 5 mg vs. hydrochlorothiazide (HCTZ) 25 mg, in hypertensive patients with Fontaine stage II (intermittent claudication). The primary endpoint was the initial claudication distance (ICD) during treadmill exercise after 24-week treatment in the per protocol population, using a noninferiority statistical approach. A total of 177 patients (mean age was 66.3 ± 9.2 years, 76.7% men) were randomized to study treatment and 127 completed the study; the intent-to-treat (ITT) analysis was performed on 163 patients, the per protocol analysis on 127 patients. Both drugs lowered blood pressure significantly. After 24-week treatment, ICD increased in the Neb group in the ITT population by 28.3% (95% CI 15.6-41.0) vs. in the HCTZ group by 26.5% (14.4-38.5), and in the per protocol population in the Neb group by 26.4% (13.4-39.4) vs. in the HCTZ group by 32.1% (18.4-45.7). Thus, noninferiority of Neb could neither be confirmed nor rejected. An increase of absolute claudication distance (ACD, mean percentage increase after 24 weeks on Neb 15.8 ± 33.2 vs. on HCTZ 20.2 ± 46.6) was observed without statistical differences between groups. Ankle-brachial index (ABI) increased slightly in both groups. Generally, both treatments were well tolerated. - Conclusion - The increases in ICD, ACD and ABI with nebivolol suggest that this medication does not have negative effects on hypertensive patients with symptomatic PAD, and can be used for treatment of hypertension in these patients at high cardiovascular risk without reducing the walking ability.